Are we living the end of democracy? A defence of the ‘free’ time of the university and school in an era of authoritarian capitalism - Säfström, Carl Anders (CONJECTURA: Filosofia e Educação, 2020)
In this article I address education beyond individualism, elitism and instrumentalism and instead understand education as central for a democratic way of life. I discuss the role of education in the making of democratic forms of life in the university, in the school as well as in other contexts outside institutions. I argue for the importance of defending the “free time” of the university and school against a “time of production” as a defining characteristic of university and school. I will show how a time of production undermine the very possibility of education, and which therefore also tends to negate pluralist democracy.